TYPE IC CHOLEDOCHAL CYST PRESENTING AN EXTRAHEPATAL CHOLESTASIS IN A 3 YEAR OLD BOY - Reza, Muhammad; Nesa, Nyoman Metriani; Putra, I Gusti Ngurah Sanjaya; Karyana, I Putu Gede; Darmajaya, Made (Medicina, 2015)
Choledochal cyst is a rare congenital dilatation of the bile ducts, mostly diagnosed in childhood. Whenappropriate resection is not performed, cholangiocarcinoma may occur in a high incidence within thesecond decade of life. This report aims to present a rare case in experience of diagnosis and managementtype IC choledochal cyst in children. We present case of a 3-year-old boy who came with jaundice anditchy skin, abdominal pain, brownish urine, pales colored of stool. Abdominal ultrasonography andcomputed tomography scan revealed type IC choledochal cyst. Patient underwent complete cyst removalsurgery and bilioenteric anastomosis through Roux-en-y hepaticojejunostomy. Excision biopsy confirmedthe diagnosis of type IC choledochal cyst. Post surgical follow up shown good physical and laboratorycondition  and  there was no  recurrence  of  symptoms. Early  surgical  procedure  through Roux-en-yhepatojejunostomy, has been performed. Long  term  follow up also  facilities good prognostic  to  thepatient. [MEDICINA 2015;46:56-60]. Kista  koledokus  adalah merupakan  penyakit  saluran  empedu  bawaan  yang  jarang  dijumpai  danbanyak terdiagnosis pada saat usia anak-anak. Tindakan berupa reseksi kista adalah yang terpentingdilakukan,  jika  tidak  segera  dilakukan  maka  dapat  meningkatkan  resiko  terjadinyacholangiocarcinoma dalam usia dekade kedua penderita dalam kehidupan. Tujuan kasus ini dilaporkanuntuk menggambarkan pengalaman dalam mendiagnosis dan tata  laksana kista koledokal tipe ICyang jarang pada anak-anak. Laporan kasus ini pada anak laki-laki berumur 3 tahun dengan keluhankulit tampak kuning dan gatal, nyeri perut, urin berwarna kecoklatan, tinja yang pucat. Ultrasonografidan CT  scan abdomen memperlihatkan adanya kista koledokus. Tindakan bedah  eksisi kista dananastomosis bilioenterik dengan menggunakan tehnik hepatojejunostomi Roux-en-y. Diagnosa kistakoledokus  tipe  IC  terkonfirmasi  saat  tindakan  eksisi biopsi. Evaluasi  setelah dilakukan  tindakanbedah memperlihatkan hasil yang bagus, baik dari pemeriksaan fisik maupun pemeriksaan penunjangdan hilangnya keluhan yang ada sebelumnya. Walaupun prosedur tindakan hepatojejunustomi Roux-en-y secara dini telah dilakukan, penderita masih membutuhkan evaluasi dalam jangka waktu yanglama. [MEDICINA 2015;46:56-60].
Keywords: choledochal cyst, children, surgery